(untitled) (Al-Academy, 2025)
Aesthetic design is an important part of chair design and it must be attractive and appropriate for the place in which it will be placed, and fit with the general décor and desired mood. The research contained four chapters, the first included a review of the problem with the following question: What are the aesthetics of chair design for people with special needs? As for the second chapter: It included two sections, the first: aesthetics and design between concept and operation, and the second: people with special needs. The third chapter: included a review of the research methodology. As for the fourth chapter: the results of the research and a set of conclusions were presented, and the study concluded with sources.